Livestock Disease and Health Care Facility in Sundarbans Delta of India - Samares Kumar Das; Hema Tripathi (Indian Journal of Extension Education, 2013)
There are a number of livestock diseases which are seasonal in nature. Understanding the disease pattern and health care facility has an implication in formulating an efficient and effective disease management strategy. With this implication, a study was conducted in four villages of Sundarban delta of India to understand the prevalence of livestock disease, their seasonality, and health care facility available. A participatory case study method was used for the study. Data were collected using semi-structured interview, listing, narrative and observation method. Study reveals that foot and mouth disease, ranikhet disease, chicken pox, hump sore, etc. were highly seasonal, whereas amphistomiasis, delayed expulsion of placenta, dystokia, etc. were not seasonal. Quacks, veterinary officers, medicine pedlars, medicine shop keepers, midwives, and ethno-veterinarians were the veterinary service providers in the study area. It is concluded that a holistic research is needed on documentation and validation of major livestock diseases in order to suggest effective disease management practices in the context of prevailing health care practices and available veterinary facilities.